1980
DOI: 10.1002/jclp.6120360204
|View full text |Cite
|
Sign up to set email alerts
|

MMPI profiles of men referred for a pretrial psychiatric assessment as a function of offense type

Abstract: Gathered MMPI and demographic data on six groups of 25 men each who had been remanded by the courts to a maximum security psychiatric hospital for pretrial assessment. The groups differed according to offense type: Murder or attempted murder of a family member or girlfriend, murder or attempted murder of an unrelated victim, rape, arson, child molesting, or property. The MMPI profiles of the groups were remarkably similar, and the prediction that the murder family group would have the highest Overcontrolled Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
1
2

Year Published

1984
1984
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 17 publications
4
26
1
2
Order By: Relevance
“…Few researchers report direct empirical comparisons of the relationship between personality variables and different styles of offending. Of the limited number of studies that do address this issue, most have used clinical personality measures and produce mixed evi-dence of any differential relationship (Fraboni, Cooper, Reed & Saltstone, 1990;Kemph, Braley & Ciotola, 1998;Nesca, 1998;Quinsey, Arnold & Pruesse, 1980).…”
Section: A Focus On Processmentioning
confidence: 98%
“…Few researchers report direct empirical comparisons of the relationship between personality variables and different styles of offending. Of the limited number of studies that do address this issue, most have used clinical personality measures and produce mixed evi-dence of any differential relationship (Fraboni, Cooper, Reed & Saltstone, 1990;Kemph, Braley & Ciotola, 1998;Nesca, 1998;Quinsey, Arnold & Pruesse, 1980).…”
Section: A Focus On Processmentioning
confidence: 98%
“…(for review, see Langevin et al, 1990aLangevin et al, , 1990b. Research examining the MMPI of sex offenders, regardless of fantasy proneness, suggests that there is no one profile or personality type that describes sex offenders as a group (Bradford, Bloomberg, & Bourget, 1988;Hall, 1989;Hall, Maiuro, Vitaliano, & Proctor, 1986;Langevin, 1983;Mann, Stenning, & Borman, 1992;Quinsey, Arnold, & Preusse, 1980;Rosen, 1974;Velasquez, Callaghan, & Carillo, 1989). This is not surprising considering the heterogeneity of sex offenders.…”
mentioning
confidence: 91%
“…Bradford, Bloomberg, & Bourget,1988;Hall, 1989b;Hall, Maiuro, Vitaliano, & Proctor, 1986: Langevin, 1983Rosen, 1974). Quinsey, Arnold, and Preusse ( 1980), for example, compared 6 groups of 25 'mentally disordered' men in a maximum security psychiatric hospital, including rapists and child molesters, and nonsex offenders. They found that the MMPI did not distinguish the 6 groups, although there were substantial numbers with clinically significant scale elevations.…”
Section: Sexual Preferencesmentioning
confidence: 98%